The Chest Physiotherapy to Manage Respiratory Rate In Patients with Bronchopneumonia: A Literature Review: Indonesia - Bisma Yudha, Magenda; Wardoyo, Eko (Java Nursing Journal, 2023)
Purpose: Knowing the application of chest physiotherapy techniques can manage respiratory rates in children with bronchopneumonia. Methods: This review uses the literature review method. Searches were conducted in PubMed, Garuda, and Google Scholar. The search strategy used keywords with "bronchopneumonia", "chest", "physiotherapy", "respiratory rate". Findings: There were eight articles reviewed in this literature review. Seven articles discussed the application of chest physiotherapy and one article discussed the combination of nebulization therapy and chest physiotherapy in bronchopneumonia or pneumonia patients in children. The overall results of this review show that the application of chest physiotherapy in airway clearance problems in children with bronchopneumonia or pneumonia is effective in removing sputum, diluting sputum, and stabilizing hemodynamic status. Conclusions: The application of chest physiotherapy in children with bronchopneumonia or pneumonia has been shown to stabilize hemodynamic status such as pulse frequency, respiratory rate frequency, oxygen saturation within normal limits, and can remove secretions, sputum, and reduce cough frequency.